Abuse of Ministerial Authority, Systemic Perjury, and Obstruction of Justice: Corruption in the Shadows of Organizational Practice - Voliotis, Seraphim (2011)
Organizational corruption has recently attracted considerable scholarly attention, especially since its devastating effects following recent major corporate scandals, the worldwide economic crisis of 2009, and the current European Union monetary crisis. This paper is based on the analysis of three distinct, yet contextually related, case studies in a European Union member state: (a) an incident of corruption by a minister in an adjudicative role, (b) widespread financial misreporting and perjury within an organization, and (c) abuse of due process and obstruction of justice by civil servants within a ministry. These cases serve to illustrate, for the first time, Aguilera and Vadera’s (in J Bus Ethics 77:431–449, 2008) framework of organizational corruption, which relates distinct types of a corrupter’s opportunity, motivation, and justification with the type of corruption present in the organization. Furthermore, the data suggest how the framework may be extended and reveal conceptual issues that require reconciliation. This study attempts such reconciliations and offers some suggestions on how the findings may be utilized by policy reformers or corruption controllers.
Keywords: bureaucratic corruption; Political corruption; Justification; Motivation; Opportunity; organizational corruption; Authority